Healing of intrabony defects using a novel human recombinant amelogenin a preclinical study - Chackartchi Tali (QUINTESSENCE INTERNATIONAL, 2023)
OBJECTIVE: To histologically evaluate the effects of a novel human recombinant amelogenin (rAmelX) on periodontal wound healing/regeneration in intrabony defects. METHOD AND MATERIALS: Intrabony defects were surgically created in the mandible of three minipigs. Twelve defects were randomly treated with either rAmelX and carrier (test group) or with the carrier only (control group). At 3 months following reconstructive surgery, the animals were euthanized, and the tissues histologically processed. Thereafter, descriptive histology, histometry, and statistical analyses were performed. RESULTS: Postoperative clinical healing was uneventful. At the defect level, no adverse reactions (eg, suppuration, abscess formation, unusual inflammatory reaction) were observed with a good biocompatibility of the tested products. The test group yielded higher values for new cementum formation (4.81 ± 1.17 mm) compared to the control group (4.39 ± 1.71 mm) without reaching statistical significance (P = .937). Moreover, regrowth of new bone was greater in the test compared to the control group (3.51 mm and 2.97 mm, respectively, P = .309). CONCLUSIONS: The present results provided for the first-time histologic evidence for periodontal regeneration following the use of rAmelX in intrabony defects, thus pointing to the potential of this novel recombinant amelogenin as a possible alternative to regenerative materials from animal origins.